2015
DOI: 10.3892/ol.2015.3827
|View full text |Cite
|
Sign up to set email alerts
|

CT pelvimetry and clinicopathological parameters in evaluation of the technical difficulties in performing open rectal surgery for mid-low rectal cancer

Abstract: The present study aimed to evaluate the predictive value of pelvic anatomical and clinicopathological parameters for use in the estimation of the likely technical difficulties that may be encountered when performing open rectal surgery for mid-low rectal cancer. Sixty consecutive patients, undergoing open rectal surgery for mid-low rectal cancer were recruited between June 2009 and April 2014. All of the surgical procedures conducted, were low anterior resection (LAR) or abdominoperineal resection (APR). The o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
32
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 15 publications
5
32
2
Order By: Relevance
“…In the literature, other MRI‐based studies identified patient‐ and tumour‐related predictors of surgical difficulty . Most of them found an association between male sex and risk of conversion from laparoscopy to laparotomy , or greater tumour volume with longer operative times .…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, other MRI‐based studies identified patient‐ and tumour‐related predictors of surgical difficulty . Most of them found an association between male sex and risk of conversion from laparoscopy to laparotomy , or greater tumour volume with longer operative times .…”
Section: Discussionmentioning
confidence: 99%
“…The physical anatomical characteristics of the Vietnamese people are similar to those of other East Asian populations, with a deep and narrow pelvis ( 5 , 6 ). Even among female patients, obesity is rare; however, large tumors, which are identified in most cases, are the primary causes of late diagnosis ( 7 ).…”
Section: Introductionmentioning
confidence: 62%
“…Laparoscopic surgery is being used widely as compared to open surgery. With the development of surgical techniques, surgeons realized that the narrow space of the pelvis significantly restricted the operation of rectal cancer surgery, and even affected the surgical outcomes [ 17 19 ]. The nature of the tumor, the extent of the disease, and anatomical description of disease should be established prior to surgery.…”
Section: Discussionmentioning
confidence: 99%